The Impact of Social Environment on Juvenile Delinquency in Tanjung Baru Subdistrict - Putra, Eka (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
In society, the phenomenon of juvenile delinquency is a serious concern because it can have a negative impact on individuals and their environment. One factor that is believed to play a role in the emergence of juvenile delinquent behavior is the social environment around them. Tanjung Baru sub-district, as an area that has certain social characteristics, is interesting to be the focus of research in identifying the impact of the social environment on juvenile delinquency. The main objective of this study is to analyze the impact of the social environment on juvenile delinquency in Tanjung Baru Sub-district. This study aims to determine the extent to which social environmental factors such as family, school, and peers affect the level of juvenile delinquency in the area. The methods to be used in this research are survey method and qualitative analysis. A survey will be conducted to collect data on the social characteristics of adolescents and their level of delinquency. In addition, in-depth interviews with teenagers, parents, teachers, and community leaders will be conducted to gain a deeper understanding of the social environmental factors that influence juvenile delinquency. The results of this study indicate a significant relationship between the social environment and the level of juvenile delinquency in Tanjung Baru Sub-district. Factors such as family disintegration, lack of supervision from parents, and negative influence from peers have a major contribution to the increase in juvenile delinquency in the area. Based on the results of the study, it can be concluded that the social environment plays an important role in shaping juvenile delinquent behavior. Therefore, efforts to reduce the level of juvenile delinquency in Tanjung Baru Sub-district should involve various parties, including families, schools, and local communities, to create a healthier environment and support positive adolescent development.